Financially independent public transport; its impacts on the public transport system in the Netherlands - van Goeverden, Kees; Peeters, Paul (European Journal of Transport and Infrastructure Research, 2005)
The paper deals with the question of how suspension of the subsidies for public transport operations in the Netherlands would affect the public transport system. Today, the costs of public transport far exceed the revenues, particularly in urban and regional transport. The most efficient measures for improving the financial performance are reducing the wages and increasing vehicle speed, for instance by enlarging stop spacing. In order to find the effects of suspension of the subsidies, two scenarios are developed describing opposite extremes that define probable developments in Dutch public transport. In both scenarios, suspension of subsidies would have strong negative effects on the urban and regional transport supply. The level of service would decline and fares would increase substantially. As a consequence the demand would fall. Long distance transport might be less affected. The effects might even be positive, depending on the strategy of the operators.